2005
DOI: 10.1097/01.alc.0000167740.19702.8c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melanocortin Receptor Activation and Blockade on Ethanol Intake: A Possible Role for the Melanocortin-4 Receptor

Abstract: Background-The melanocortin (MC) system is composed of peptides that are cleaved from the polypeptide precursor proopiomelanocortin. A growing body of literature suggests that the MC system modulates neurobiological responses to drugs of abuse. Because ethanol has direct effects on central proopiomelanocortin activity, it is possible that MC neuropeptides participate in the control of voluntary ethanol consumption. Here we assessed the possibility that MC receptor (MCR) agonists modulate ethanol intake via the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
71
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(84 citation statements)
references
References 76 publications
11
71
2
Order By: Relevance
“…MC neuropeptides, in the brain, act through at MC3 receptor (MC3R) and MC4R (Cone). Central administration of potent non-selective MCR agonist melanotan-II (MTII) and a selective MC4R agonist significantly reduced voluntary ethanol in adult mice and rats (Navarro et al, 2005(Navarro et al, , 2011Lerma-Cabrera et al, 2012), but not MTII administration in Mc4r-/-mice (Navarro et al, 2011). Central AgRP and HS014, MC4R antagonist administration increases voluntary ethanol consumption in mice and rats (Navarro et al, 2005;Lerma-Cabrera et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…MC neuropeptides, in the brain, act through at MC3 receptor (MC3R) and MC4R (Cone). Central administration of potent non-selective MCR agonist melanotan-II (MTII) and a selective MC4R agonist significantly reduced voluntary ethanol in adult mice and rats (Navarro et al, 2005(Navarro et al, , 2011Lerma-Cabrera et al, 2012), but not MTII administration in Mc4r-/-mice (Navarro et al, 2011). Central AgRP and HS014, MC4R antagonist administration increases voluntary ethanol consumption in mice and rats (Navarro et al, 2005;Lerma-Cabrera et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…At least 28 peptides are known to be involved in food and water intake, and several of these have also been implicated in ethanol consumption. These include galanin, neuropeptide Y (NPY), melanin concentrating hormone, the opioids, and a-melanocyte stimulating hormone (Bodnar and Klein, 2005;Duncan et al, 2005;Gilpin et al, 2004;Haddad, 2004;Kokare et al, 2006;Lewis et al, 2005;Navarro et al, 2005;Rada et al, 2004;Thiele et al, 2004). In addition to replicating the effects of galanin, the present report expands this area of research to include 2 other orexigenic peptides of current interest, orexin-A and ghrelin.…”
mentioning
confidence: 81%
“…Injection of an MC4R selective agonist into the VTA and nucleus accumbens decreased ethanol intake (Lerma-Cabrera et al, 2012), and both MTII and an MC4R-selective agonist continued to decrease ethanol intake in MC3R knockout mice (Navarro et al, 2005), whereas MTII had no effect on ethanol intake in MC4R knockout mice (Navarro et al, 2011). Thus, it appears that ␣MSH can activate MC4Rs in multiple corticolimbic regions to decrease alcohol intake, whereas AgRP antagonism of MC4R activity leads to increased alcohol intake.…”
Section: Melanocortins and Drug Rewardmentioning
confidence: 96%
“…Icv injection of MTII decreased ethanol intake (Navarro et al, 2005(Navarro et al, , 2003Ploj et al, 2002), while icv injection of AgRP increased ethanol intake (Navarro et al, 2005), although this effect has not been observed in all studies (Navarro et al, 2003;Ploj et al, 2002). Furthermore, AgRP knockout mice show decreased ethanol intake, decreased ethanol self-administration, and decreased binge-like intake of ethanol (Navarro et al, 2009).…”
Section: Melanocortins and Drug Rewardmentioning
confidence: 97%
See 1 more Smart Citation